Landslides and lateral spreading triggered by the 24 January 2020 Sivrice earthquake (East Anatolian Fault) - Köküm, Mehmet (Gumushane University, 2021)
On 24 January 2020, a devastating earthquake struck the town of Sivrice in Elazığ province at 20:55 local time (17:55 UTC), resulting in 41 death and significant loss of property. The magnitude of the earthquake was determined to be Mw 6.8 and strong shaking of main shock lasted about 20 seconds. The Sivrice earthquake triggered about 30 landslides over an area of ~55 km2. This article presents the preliminary results of comprehensive study on mapping of the distribution of landslides, lateral spreading and other ground damaged effects triggered by the Sivrice earthquake occurred on the East Anatolian Fault. Following Sivrice earthquake, based on detailed on-ground field studies: (1) The Sivrice earthquake produced fewer landslides than empirical prediction for shallow earthquakes of these magnitudes (Mw 6.8) would suggest; (2) the Sivrice earthquake triggered extensive lateral spreading in Holocene age river banks, and result in the ground tears, opening surface cracks and fissure on flat ground; (3) primary surface rupture was not produced by Sivrice earthquake. © 2021, Gumushane University. All rights reserved.
24 Ocak 2020 Sivrice depreminin (Doğu Anadolu Fayı) tetiklediği heyelan ve yanal yayılmalar
Keywords: Earthquake; East Anatolian Fault; Landslide; Lateral spreading